Control of separate pathogenic autoantibody responses marks MHC gene contributions to murine lupus - Vyse, Timothy J. (The National Academy of Sciences, 1999)
Previous studies have suggested that MHC and non-MHC genes contribute to the development of autoimmune disease in F(1) hybrids of New Zealand black (NZB) and white (NZW) mice. We conducted a genome-wide screen of 148 female (NZB × NZW)F(1) × NZB backcross mice to map dominant NZW genetic loci linked with lupus disease traits. In this backcross analysis, inheritance of the NZW MHC (H2(d/z) vs. H2(d/d)) was strongly linked with the development of lupus nephritis (P ≈ 1 × 10(−16)), increasing the risk of disease by over 30-fold. H2(d/z) was also linked with elevated serum levels of IgG autoantibodies to single-stranded DNA, double-stranded DNA, histones, and chromatin but not with anti-gp70 autoantibodies, measured as circulating gp70–anti-gp70 immune complexes. Non-MHC contributions from NZW seemed weak in comparison to MHC, although NZW loci on chromosomes 7 and 16 were noted to be suggestively linked with autoantibody production. Strikingly, H2(d/z) (compared with H2(d/d)) enhanced antinuclear antibodies in a coordinate fashion but did not affect anti-gp70 production in the current backcross. However, the opposite influence was noted for H2(d/z) (compared with H2(z/z)) when (NZB × NZW)F(1) × NZW backcross mice were analyzed. These results suggest that H2(z) and H2(d) haplotypes differentially regulate two different sets of nephritogenic autoantibody responses. This study confirms a critical role for H2(z) compared with other dominant NZW loci in (NZB × NZW)F(1) mice and provides an explanation as to why H2(d/z) heterozygosity is required for full expression of disease in this model.